Healthcare Workers’ Perceptions of Patient Safety Culture in United States Hospitals: A Systematic Review and Meta-Analysis - Chilukuri, Ganesh; Westerman, S. Thomas (International Journal of Medical Students, 2024)
Background: Despite leading in healthcare spending, the United States sees only marginal improvements in patient outcomes among developed nations. Assessing patient safety culture (PSC) through the Hospital Survey on Patient Safety Culture (HSOPSC) provides insights into overall patient safety and attitudes toward medical errors. This study aims to examine PSC in U.S. hospitals across professional categories via a systematic review and meta-analysis of published literature. Methods: Embase, PubMed (Medline), Web of Science, Scopus, and AHRQ’s Bibliography were consulted for identifying studies. A total of 31 articles met the eligibility criteria for inclusion, which garnered 608,443 survey participants in a national population of hospital healthcare professionals. For each professional category of PSC, a fixed and random-effects meta-analysis was performed, and a subgroup analysis was also conducted to measure differences in perceptions of PSC based on type of healthcare professional. Results: The HSOPSC composite average across all the studies was 61.3% positive responsiveness, indicating a need for improvement in patient safety. “Teamwork within units” had the highest positive PSC perception while “nonpunitive response to error” and “handoffs and transitions” scored the lowest. Furthermore, healthcare trainees and physicians seemed to have overall worse perceptions of patient safety culture compared to other professional subgroups, indicating the potential impacts of inexperience and a culpability culture on patient safety and medical error in hospitals. Discussion: To strengthen weak aspects of patient safety culture, hospitals should implement interventions such as teamwork training and error-reporting systems, thereby enhancing patient safety measures and reducing medical errors.